Análise do uso de recursos pedagógicos lúdicos no desempenho de escolas de ensino fundamental do município de Santarém, Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The educator, in general, needs to follow the technological changes of teaching. The present work focuses on the use of leisure resources in public and private schools in the city of Santarem -Para, Brazil. The study was based on a survey of fifteen municipal public education institutions and five private institutions, verifying their applicability by teachers and analyzing the results as to their relevance in content absorption, considering the performance of the students, regarding the teachers who apply in relation to those who do not work with the game, and which games are used by them. In the data collection, questionnaires were used with the teachers of which they teach in primary, secondary and also in the support rooms. The results of the survey were analyzed and capitalized through graphs in microsoft excel® 2010 software. When examining the collected data, it is verified that the teaching of teaching in a playful way is not to waste time but to learn in a pleasurable way to awaken a conception of learning in the student, a different way of assimilating contents through creativity, quick thinking, interest and understanding of the process leading to efficient results.
Keywords: Jogos Lúdicos; Ensino; Educação; Escolas; CNPQ:: CIÊNCIAS BIOLÓGICAS